Pengaruh Edukasi Bantuan Hidup Dasar dengan Media Audio Visual terhadap Pengetahuan Pengawas Kolam Renang di Kabupaten Purbalingga - Dina Siti Nurjanah; Sri Suparti (Faletehan Health Journal, 2022)
Drowning is a condition where the body is immersed in water, causing respiratory system disturbances which can be fatal and leads to death. A provision of Basic Life Support (BLS) in drowning cases is very important for the victims’ life. Drowning can be occured in water tourism areas, one of which is a swimming pool, thus, it is very significant to provide education to increase BLS knowledge of pool lifeguards. Knowledge of BLS can be obtained through various methods using technological advances, including audio-visual media. The objective of this study was to determine the effects of BLS education using audio visual media on the knowledge of pool lifeguards in Purbalingga Regency. This study utilized a quantitative method with a pre-experimental design covering one group pre-test post-test design. The population in this study were all pool lifeguards at Tirto Asri Walik Swimming Pool and at Bojongsari Water Tourism Object. The total sampling technique was used to select 31 respondents. The instrument for data collection was a questionnaire and the Wilcoxon test was used for further data analysis. The result indicated that the mean value was 73.23 before the treatment. Meanwhile, after the treatment, the mean value increased to 82.58 with p value < 0.001. BLS education by audio-visual media increases the knowledge of pool lifeguards in Purbalingga Regency.